PENGARUH KEPEMILIKAN INTITUSIONAL DAN KUALITAS AUDIT TERHADAP EARNINGS MANAGEMENT DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL MODERASI - Sri Ayem; Yuliana Adelheit Knoba (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2021)
This research aims to determine the effect of institutional ownership and audit quality on earnings management with financial distress as a moderating variable. The research sample was selected using a purposive technique and taken were the annual financial reports of manufacturing companies that were registered consistently during the last four years, namely 2016-2019 with a sample size of 14. The results of this study indicate that institutional ownership has a negative and significant effect on earning management, audit quality has a negative effect on earnings management, financial distress can moderate the relationship between institutional ownership and earnings management, financial distress can moderate the relationship between audit quality and earnings management